Community-based WASH and CERIA-PHBS Model for Post-Flood Health Recovery in Rural Aceh - Teungku Nih Farisni; Yaemaliza; Safrizal; Arrazy Elba Ridha; Fitriani; Zakiyuddin; Fitrah Reynaldi (Society : Jurnal Pengabdian Masyarakat, 2026)
This community engagement program was implemented in Lawet Village, West Aceh, a flood-prone rural area severely affected by the November 26, 2025 disaster, which resulted in environmental degradation, limited access to safe water, inadequate sanitation facilities, low adoption of clean and healthy living behaviors (PHBS), and the absence of safe educational spaces for children. The program aimed to improve post-disaster community health resilience through an integrated community-based approach combining Water, Sanitation, and Hygiene (WASH) interventions with the CERIA-PHBS (Cerdas, Edukatif, Interaktif, dan Aman) model. The program was conducted through five stages: socialization, participatory assessment, technology implementation, mentoring and evaluation, and sustainability planning. Key interventions included the installation of a community-based clean water system, provision of ≥10 portable handwashing stations (CTPS), health education for families, and the establishment of a child-friendly educational space. A pre–post descriptive evaluation was used to assess changes in knowledge and behavior. The results showed significant improvements, including increased access to clean water, improved PHBS practices from approximately 25% to ≥70%, enhanced community knowledge, and strengthened capacity of ≥10 health cadres. In addition, more than 60 children participated in CERIA-PHBS activities, with improved hygiene behavior and psychosocial well-being. This integrated model demonstrates effectiveness in accelerating post-flood health recovery and offers a scalable and sustainable approach for disaster-prone rural communities.